2022
DOI: 10.1093/pcp/pcac020
|View full text |Cite
|
Sign up to set email alerts
|

CsIVP Modulates Low Nitrogen and High-Temperature Resistance in Cucumber

Abstract: Crop plants experience various abiotic stresses that reduce yield and quality. Although several adaptative physiological and defense responses to single stress have been identified, the behavior and mechanisms of plant response to multiple stresses remain underexamined. Herein, we determined that the leaf and vascular changes in CsIVP-RNAi cucumber plants can enhance resistance to nitrogen deficiency and high-temperature stress. CsIVP negatively regulated high nitrate affinity transporters (NRT2.1, NRT2.5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…As a TF, MBF1c may generally bind to specific DNA sequences . Since CsMBF1c has no transcriptional activation (Figure ), this suggests that CsMBF1c may act as a key transcriptional cofactor by combining TFs to regulate the tolerance of cucumber to heat. , CsMBF1c can interact with CsDREB2 and CsNFYA1 in organisms (Figures and S5). DREB2 plays an important role in the regulatory network of the responses to high temperatures. , In addition, DREB2 has been reported to coactivate heat-related genes with NFYA2/B3/DPB3-1 trimers in Arabidopsis . , NF-YA primarily regulates various life processes by binding to other proteins to form complexes in plants. In cucumber, CsNFYA1 is involved in the regulation of flowering .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a TF, MBF1c may generally bind to specific DNA sequences . Since CsMBF1c has no transcriptional activation (Figure ), this suggests that CsMBF1c may act as a key transcriptional cofactor by combining TFs to regulate the tolerance of cucumber to heat. , CsMBF1c can interact with CsDREB2 and CsNFYA1 in organisms (Figures and S5). DREB2 plays an important role in the regulatory network of the responses to high temperatures. , In addition, DREB2 has been reported to coactivate heat-related genes with NFYA2/B3/DPB3-1 trimers in Arabidopsis . , NF-YA primarily regulates various life processes by binding to other proteins to form complexes in plants. In cucumber, CsNFYA1 is involved in the regulation of flowering .…”
Section: Discussionmentioning
confidence: 99%
“…32 Since CsMBF1c has no transcriptional activation (Figure 7), this suggests that CsMBF1c may act as a key transcriptional cofactor by combining TFs to regulate the tolerance of cucumber to heat. 10,35 CsMBF1c can interact with CsDREB2 and CsNFYA1 in organisms (Figures 7 and S5). DREB2 plays an important role in the regulatory network of the responses to high temperatures.…”
Section: Csmbf1c Has Conserved Gene Properties and Affected The Photo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic lines overexpressing NRT1.7 in Arabidopsis , rice and tobacco plants exhibited increased NO 3 − accumulation in growing tissues by recycling N from older leaves (Chen et al, 2020). Yan et al (2022) showed that RNAi‐mediated silencing of IRREGULAR VASCULATURE PATTERNING ( IVP ) in Cucumis sativus promotes plant tolerance to N deficiency and high‐temperature stress by negatively regulating the expression of NO 3 − transporters (NRT2.1 and NRT2.5) and recyclers (NRT1.7, NRT1.9 and NRT 1.12) under low NO 3 − conditions. NRT2.4 and NRT2.5 are highly expressed in major and minor veins for the removal of apoplastic NO 3 − under low N supply for phloem transport (Kiba et al, 2012; Lezhneva et al, 2014).…”
Section: Regulation Of N Allocation To Vegetative and Reproductive Br...mentioning
confidence: 99%
“…It prefers warm temperatures, but when the temperature surpasses 35°C, the growth of cucumbers is impeded (Woycicki et al, 2011; Chen et al, 2021). When ambient temperatures reach 50°C, leaf and stem undergo rapid wilting, root growth is retarded, pollen viability is diminished, the fruit is deformed, and it might even result in plant death, all leading to compromised fruit quality and commodity yield (Yu et al, 2018; Liu et al, 2021; Yan et al, 2022; Yu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%